2010
DOI: 10.1348/000712609x467891
|View full text |Cite
|
Sign up to set email alerts
|

A test of engagement versus disengagement in catastrophe models

Abstract: The present study explored the interactive effects of self-efficacy and increasing/decreasing task difficulty upon engagement and disengagement within a cusp-catastrophe model framework. Using a closed motor skill aiming task participants (N=60) were required to compete in conditions where task difficulty increased and then decreased (or vice versa) where they were rewarded for good performance but penalized for bad. Participants who reported low levels of self-efficacy disengage at an earlier level of task di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…First, in anxiety, the absence of a real threat or the inappropriateness of fight-or-flight behavior renders physiological changes (Barrett and Armony, 2006). Second, considering the argument of Beattie and Davies (2010), it can be suggested that the relationship between cognitive anxiety and psychophysiological arousal might be mediated by self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…First, in anxiety, the absence of a real threat or the inappropriateness of fight-or-flight behavior renders physiological changes (Barrett and Armony, 2006). Second, considering the argument of Beattie and Davies (2010), it can be suggested that the relationship between cognitive anxiety and psychophysiological arousal might be mediated by self-confidence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the Cusp Catastrophe Model (CCM; Hardy, 1990) offers an intuitively appealing account of choking, as it does provide an explanation for the significant/catastrophic drop in performance associated with a choke (Hill et al, 2009). According to the CCM, the interactive effects of cognitive anxiety, physiological arousal (Hardy, 1990), effort (Hardy, Beattie, & Woodman, 2007) and self-confidence (Beattie & Davies, 2010) may influence the likelihood of a catastrophic performance failure, that could include the choke. Thus, more research regarding a potential relationship between the tenets of CCM and the choking phenomenon is required.…”
Section: Discussionmentioning
confidence: 99%
“…Although the model is diffi cult to test empirically and has received criticism (see Tenenbaum & Becker, 2005), it does provide an elegant framework to explain how clutch performance and choking can occur under high pressure. Furthermore, one of the strengths of the model is that diff erent control parameters can be selected to examine other potential interactions in performance disruption (e.g., Beattie & Davies, 2010;Hardy, Beattie, & Woodman, 2007). Cheng et al's (2009) framework is a recent attempt at reconceptualizing performance anxiety, due in part to a concern that the adaptive nature of anxiety had been under-represented in the sport psychology literature.…”
Section: Processing Efficiency Theorymentioning
confidence: 99%